2022
DOI: 10.48550/arxiv.2201.02936
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weak Supervision for Affordable Modeling of Electrocardiogram Data

Abstract: Analysing electrocardiograms (ECGs) is an inexpensive and non-invasive, yet powerful way to diagnose heart disease. ECG studies using Machine Learning to automatically detect abnormal heartbeats so far depend on large, manually annotated datasets. While collecting vast amounts of unlabeled data can be straightforward, the point-by-point annotation of abnormal heartbeats is tedious and expensive. We explore the use of multiple weak supervision sources to learn diagnostic models of abnormal heartbeats via human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Answering such questions is often easier, yields more reliable labels, and requires less annotation effort to achieve equivalent performance. We have also demonstrated how to completely avoid the laborious process of pointillistic labeling of reference data for clinical applications of AI using weak supervision [ 49 ]. By harvesting multiple labeling functions that a human expert would use in their mind to assess each case at hand, one can automate the process of data annotation.…”
Section: Examples Of Forecasting and Phenotyping Instability In The Icumentioning
confidence: 99%
See 1 more Smart Citation
“…Answering such questions is often easier, yields more reliable labels, and requires less annotation effort to achieve equivalent performance. We have also demonstrated how to completely avoid the laborious process of pointillistic labeling of reference data for clinical applications of AI using weak supervision [ 49 ]. By harvesting multiple labeling functions that a human expert would use in their mind to assess each case at hand, one can automate the process of data annotation.…”
Section: Examples Of Forecasting and Phenotyping Instability In The Icumentioning
confidence: 99%
“…This is particularly appealing when facing large amounts of clinical data needing annotation. In one such exercise, we have shown that a handful of labeling functions derived from basic clinical knowledge can eliminate the need for manual data annotation and yield predictive models of performance comparable to the equivalent models trained on data point-by-point labeled by expert clinicians when evaluated on the task of detecting arrhythmia in ECG signals [ 49 ].…”
Section: Examples Of Forecasting and Phenotyping Instability In The Icumentioning
confidence: 99%